Development policies for agricultural electromechanical technologies. Case study of Nghe An Province - Quyet, Phan The (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Agricultural electromechanical technologies keep an important role in agricultural production in Vietnam actually. In addition to ease hard works of farmers, it assists to increase productivities of agricultural production. Actual situation of application of agricultural electromechanical technologies is seen as weak and lacking as required by actual needs. One of the reasons of this situation is the shortages of the system policies related to agricultural electromechanical technologies. After having analyses of strong and weak points of this system, the author proposes some solutions to enhance the application of electromechanical technologies and equipments in production. Code: 13010401